A Critical Review of Personal Statements Submitted by Dermatology Residency Applicants. (16th September 2014) - Olazagasti, Jeannette; Gorouhi, Farzam; Fazel, Nasim
Abstract : Background . A strong personal statement is deemed favorable in the overall application review process. However, research on the role of personal statements in the application process is lacking. Objective . To determine if personal statements from matched applicants differ from unmatched applicants. Methods . All dermatology residency applications (n = 332 ) submitted to UC Davis Dermatology in the year of 2012 were evaluated. Two investigators identified the characteristics and recurring themes of content present in the personal statements. Then, both investigators individually evaluated the content of these personal statements in order to determine if any of the defined themes was present. Chi-square, Fisher's exact, and reliability tests were used. Results . The following themes were emphasized more often by the matched applicants than the unmatched applicants as their reasons for going into dermatology are to study the cutaneous manifestations of systemic disease (33.8% versus 22.8%), to contribute to the literature gap (8.3% versus 1.1%), and to study the pathophysiology of skin diseases (8.3% versus 2.2%; P ≤ 0.05 for all). Conclusion . The prevalence of certain themes in personal statements of dermatology applicants differs according to match status; nevertheless, whether certain themes impact match outcome needs to be further elucidated.